Follicular GH and IGF1 Levels Are Associated With Oocyte Cohort Quality: A Pilot Study - Scheffler, Florence; Vandecandelaere, Albane; Soyez, Marion; Bosquet, Dorian; Lefranc, Elodie; Copin, Henri; Devaux, Aviva; Benkhalifa, Moncef; Cabry, Rosalie; Desailloud, Rachel (Frontiers in Endocrinology, 2021)
Introduction: Oocyte quality is a critical factor for embryo development and thus for the obtention of a pregnancy. The objective of this study was to analyze the association between oocyte cohort quality and the follicular levels of growth hormone (GH), insulin-like growth factor 1 (IGF1), 25-hydroxy vitamin D (25OHD), thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4) and antithyroid antibodies, as a function of intracytoplasmic sperm injection (ICSI) outcomes. Materiel and methods: We conducted a prospective comparative pilot study from January 2013 to December 2017. 59 ICSI cycles constituted an abnormal oocyte cohort (n=34 cycles, in which more than 50% of oocytes presented at least one morphological abnormality) and a normal oocyte cohort (n=25 cycles, in which 50% or less of the oocytes presented at least one morphological abnormality). GH, IGF1, 25OHD, TSH, fT3, fT4 and antithyroid antibodies were measured in follicular fluid. Results: The fertilization rate was lower in the abnormal oocyte cohort (65.5% vs. 80%, respectively, p=0.012). The proportion of oocytes with at least one abnormality was 79.4% in the abnormal oocyte cohort and 29.0% in the normal oocyte cohort. The mean number of morphological abnormalities per oocyte was significantly higher in the abnormal oocyte cohort. The follicular levels of GH (4.98 vs. 2.75 mIU/L, respectively; p <0.01) and IGF1 (72.1 vs. 54.2 ng/mL, respectively; p=0.05) were higher in the normal oocyte cohort. There was no association between oocyte cohort quality and follicular levels of TSH, fT3, fT4, antithyroid antibodies, or 25OHD. Conclusion: Oocyte cohort quality is associated with follicular levels of GH and IGF1.